Simple non-fused electron acceptors for efficient and stable organic solar cells - Yu, Zhi-Peng; Liu, Zhi-Xi; Chen, Fang-Xiao; Qin, Ran; Lau, Tsz-Ki; Yin, Jing-Lin; Kong, Xueqian; Lu, Xinhui; Shi, Minmin; Li, Chang-Zhi; Chen, Hongzheng (Nature communications, 2019)
The flexibility in structural design of organic semiconductors endows organic solar cells (OSCs) not only great function-tunabilities, but also high potential toward practical application. In this work, simple non-fused-ring electron acceptors are developed through two-step synthesis from single aromatic units for constructing efficient OSCs. With the assistance of non-covalent interactions, these rotatable non-fused acceptors (in solution) allow transiting into planar and stackable conformation in condensed solid, promoting acceptors not only feasible solution-processability, but also excellent film characteristics. As results, decent power conversion efficiencies of 10.27% and 13.97% can be achieved in single and tandem OSCs consisting of simple solution-cast blends, in which the fully unfused acceptors exhibit exceptionally low synthetic complexity index. In addition, the unfused acceptor and its based OSCs exhibit promising stabilities under continuous illumination. Overall, this work reveals valuable insights on the structural design of simple and effective electron acceptors with great practical perspectives. Non-fullerene electron acceptors have pushed the efficiency of organic solar cells up to 15% but they all contain fused rings and are inconvenient to synthetic access. Here Yu et al. develop fully unfused acceptors featuring non-covalent intramolecular interactions, high efficiencies and high stability.